A Nontemplated Route to Macrocyclic Dibridgehead Diphosphorus Compounds: Crystallographic Characterization of a "Crossed‐Chain" Variant of in/out Stereoisomers. Issue 18 (3rd August 2018) - Kharel, Sugam; Jia, Tiezheng; Bhuvanesh, Nattamai; Reibenspies, Joseph H.; Blümel, Janet; Gladysz, John A.
Abstract: Reactions of (O=)PH(OCH2 CH3 )2 and BrMg(CH2 ) m CH=CH2 (4.9–3.2 equiv; m =4 (a ), 5 (b ), 6 (c )) give the dialkylphosphine oxides (O=)PH[(CH2 ) m CH=CH2 ]2 (2 a –c ; 77–81 % after workup), which are treated with NaH and then α, ω‐dibromides Br(CH2 ) n Br (0.49–0.32 equiv; n =8 (a′ ), 10 (b′ ), 12 (c′ ), 14 (d′ )) to yield the bis(trialkylphosphine oxides) [H2 C=CH(CH2 ) m ]2 P(=O)(CH2 ) n (O=)P[(CH2 ) m CH=CH2 ]2 (3 ab′, 3 bc′, 3 cd′, 3 ca′ ; 79–84 %). Reactions of3 bc′ and3 ca′ with Grubbs' first‐generation catalyst and then H2 /PtO2 afford the dibridgehead diphosphine dioxides (4 bc′, 4 ca′ ; 14–19 %, n′ =2 m +2); 31 P NMR spectra show two stereoisomeric species (ca. 70:30). Crystal structures of two isomers of the latter are obtained, out, out ‐4 ca′ and a conformer of in, out ‐4 ca′ that features crossed chains, such that the (O=)P vectors appear out, out . Whereas4 bc′ resists crystallization, a byproduct derived from an alternative metathesis mode, (CH2 )12 P (=O)(CH2 )12 (O=)P(C H2 )12, as well as3 ab′ and3 bc′, are structurally characterized. The efficiencies of other routes to dibridgehead diphosphorus compounds are compared. Abstract : Coming to a head : Olefinic bis(trialkylphosphine oxides)1 can be prepared in good yields and undergo twofold intramolecular ring‐closing metatheses (Grubbs' catalyst) and hydrogenations to give modest yields of dibridgehead diphosphine oxides2, one of which exhibits a new type of in / out isomerism in the solid state (see figure).